Modelling bio-energy with carbon storage (becs) in a multi-region version of flames - Read, P.; Lermit, J.; Kathirgamanathan, P. (Greenhouse Gas Control Technologies Elsevier Science, 2003)
Global FLAMES [1,2j demonstrates the potential of the combined evolution of the stock and flow effects from temporary sequestration and subsequent fossil fuel displacement due to plantation based bio-energy, in reducing greenhouse gas levels below those widely thought to be feasible [3]. This surprising effectiveness can be further enhanced by linking plantation bio-energy to carbon capture and storage [4]. Such `BECS' technology yields, potentially, a negative emissions energy system and control of CO2 levels on a few decade time-scale. The effect of BECS is illustrated using global FLAMES. To provide relevance to country level scenario building and decision taking, FLAMES has been developed [SI into a multi-region dynamic market model simulating trade in fossil fuel, biofuel, and timber products. Results are illustrated in the case of three notional regions, 'rich', 'landed' and `popet' (populous with petroleum) — broadly equivalent to the 'North', South Sahara Africa with Southern America, and Asia plus OPEC